Plundered empire - Greenhalgh, Michael, author.
1 online resource.
Keywords: This book concentrates on the sometimes Greek but largely Roman survivals many travellers set out to see and perhaps possess throughout the immense Ottoman Empire, on what were eastward and southward extensions of the Grand Tour. Europeans were curious about the Empire, Christianity’s great rival for centuries, and plenty of information on its antiquities was available, offered here via lengthy quotations. Most accounts of the history of collecting and museums concentrate on the European end. Plundered Empire details how and where antiquities were sought, uncovered, bartered, paid for or stolen, and any tribulations in getting them home. The book provides evidence for the continuing debate about the ethics of museum collections, with 19th century international competition the spur to spectacular acquisitions.